Restricted Diffusion within Ring Enhancement Is Not Pathognomonic for Brain Abscess - Hartmann, Marius; Jansen, Olav; Heiland, Sabine; Sommer, Clemens; Münkel, Kristin; Sartor, Klaus (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Recent experience suggests that diffusion-weighted MR imaging may be decisive in the differential diagnosis of ring-enhancing cerebral lesions. Whether restricted diffusion within a ring-enhancing cerebral mass lesion is pathognomonic for abscess was studied.METHODS: Seventeen patients with ring-enhancing cerebral lesions (three abscesses, six glioblastomas, eight metastases) on conventional contrast-enhanced T1-weighted images were examined with echo-planar diffusion-weighted MR imaging. Apparent diffusion coefficient (ADC) maps and the ADCs were calculated for all lesions. Lesions with signs of intralesional hemorrhage on unenhanced T1-weighted images were excluded.RESULTS: The central portion of all six glioblastomas and seven of eight metastases showed unrestricted diffusion, whereas two of three abscesses showed restricted diffusion (low ADC values) in their cavity. However, restricted diffusion also was found in one metastasis, and one abscess within a postoperative cavity showed unrestricted diffusion within a larger nondependent portion.CONCLUSION: In patients with ring-enhancing cerebral mass lesions, restricted diffusion might be characteristic but is not pathognomonic for abscess, as low ADC values also may be found in brain metastases.